A case of acute myocardial infarction with anomalous origin of the right coronary artery from the contralateral aortic sinus - Reddy, Krupal; Patil, Sandip; Singh, Harminder (International Journal of Research in Medical Sciences, 2021)
Anomalous coronary anomalies are technically challenging. We describe the case of a 48-year-old male who suffered an acute inferior wall myocardial infarction due to thrombotic total occlusion in an anomalous right coronary artery arising from the contralateral aortic sinus.